Synchronous Multicentric Osteosarcoma in the Canine Axial Skeleton: a Report of Two Cases - Moreira, Matheus V. L.; Silva, Juneo F.; Boeloni, Jankerle N.; Ocarino, Natalia M.; Serakides, Rogéria (Brazilian Journal of Veterinary Pathology, 2014)
Two cases of axial synchronous multicentric osteosarcoma are described in male dogs 11 and 13 years of age. In both cases, the necropsy revealed multiple tumor nodules or masses in the thoracic vertebrae and ribs. The microscopic features indicated that the masses were osteoblastic osteosarcoma for all bone sites with immunohistochemical expression of vimentin and osteocalcin and the absence of cytokeratin. In both cases, multicentric osteosarcoma was considered to be present simultaneously in various bone sites of the axial skeleton, to be of the same histological type and to exhibit the same immunohistochemical characteristics in all bone sites, with no macroscopic or microscopic metastases to the lungs or any other soft tissue.